2019
DOI: 10.1038/s41467-019-12543-5
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional landscape and clinical utility of enhancer RNAs for eRNA-targeted therapy in cancer

Abstract: Enhancer RNA (eRNA) is a type of noncoding RNA transcribed from the enhancer. Although critical roles of eRNA in gene transcription control have been increasingly realized, the systemic landscape and potential function of eRNAs in cancer remains largely unexplored. Here, we report the integration of multi-omics and pharmacogenomics data across large-scale patient samples and cancer cell lines. We observe a cancer-/lineage-specificity of eRNAs, which may be largely driven by tissue-specific TFs. eRNAs are invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
277
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(300 citation statements)
references
References 63 publications
11
277
0
Order By: Relevance
“…Recently, the clinical importance of enhancers have been widely recognized, as shown in IBD (Boyd et al, 2018) and cancer studies (Zhang et al, 2019). Nevertheless, the functional roles of variants on or near enhancers are unclear, and only a few enhancer RNA QTL studies in LCL using limited number of subjects (154 European (Garieri et al, 2017) and 69 Yoruban (Kristjánsdóttir et al, 2018)) have been conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the clinical importance of enhancers have been widely recognized, as shown in IBD (Boyd et al, 2018) and cancer studies (Zhang et al, 2019). Nevertheless, the functional roles of variants on or near enhancers are unclear, and only a few enhancer RNA QTL studies in LCL using limited number of subjects (154 European (Garieri et al, 2017) and 69 Yoruban (Kristjánsdóttir et al, 2018)) have been conducted.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the normalized gene expression pro le of eRNA in BLCA (annotated by Ensemble ID) were downloaded from the eRic (enhancer RNA in cancers)database (https://hanlab.uth.edu/eRic/) 11 . In addition, the o cial gene symbol of each eRNA was identi ed by ChIPseeker packageaccordingtothelocationinhg38 genome 13 .…”
Section: The Erna Expression Matrix Extractionmentioning
confidence: 99%
“…The malfunction of enhancers may induce genetic and epigenetic alterations, and subsequently drive tumorigenesis and recurrence in many cancers 9,10 . Enhancer RNAs (eRNAs), a type of noncoding RNAs transcribed from the enhancer, help to explore the mechanisms of enhancers and also participate in cancer development 11 . Its expression is also various in different tumor types and individual patients, thus may serve as potential diagnosis markers or therapeutic targets 12 .…”
Section: Introductionmentioning
confidence: 99%
“…It is important to explore the sequence characteristics of the miRes to conduct further identification of enhancer-miRNA interactions. Previously, it was reported that eRNA can be used as a trans-acting element to participate in the regulation of target genes (14). Consequently, the human GENCODE annotation was first used to investigate the transcript types of the distal and proximal regulatory miRes.…”
Section: There Are Significant Differences In the Sequence Characterimentioning
confidence: 99%